Preparation and characterization of Melamine-Formaldehyde (MF)-bound cyclen derivatives for efficient removal of uranium [U(VI)] ions from wastewater. (February 2022) - Paz Tal, Ofra; Mizrahi, Amir; Lerner, Nadav; Gelfer, Svetlana; Columbus, Ishay; Mizrahi, Dana
Abstract: Many studies have shown successful functionalization of a polymeric matrix with different chelating moieties for metal ion removal. Melamine-Formaldehyde (MF) resin is a highly porous and robust matrix. It has appropriate chemical and physical properties to serve as a basis for an adsorbent suitable for hazardous material removal e.g., uranium. In this work, we report the synthesis and characterization of new cyclen ligands AspDOTA, GlyDOTA and PropDOTA, which are derivatives of DOTA, a well-known chelating ligand for actinide ions, and the subsequent synthesis of cyclen ligands functionalized MF resins. All new compounds were characterized ( 1 H and 13 C NMR for the ligands, MAS solid state 13 C NMR for the final functionalized polymer). This study demonstrates that U(VI) extraction efficiency of the new MF-cyclen resins depends on the nature of the ligand attached to the polymeric skeleton. It is clear that the MF-AspDOTA resin is the most efficient resin for U(VI) extraction in aqueous solution at pH = 5. Therefore, it is recommended to further investigate the MF-AspDOTA system for wastewater treatment. Graphical abstract: Unlabelled Image Highlights: The novel MF-cyclen resins offer an appealing method for chelation of uranium [U(VI)] from wastewater. U(VI) extraction efficiency depends on the nature of the ligand attached to the polymeric skeleton. MF-AspDOTA was found to be a high-performance resin with high affinity towards U(VI) ions. The MF-AspDOTA novel resin can remove 95% of U(VI) ions at pH 5 (Kd = 1808 mL/g).